A 3D finite strain model for intralayer and interlayer crack simulation coupling the phase field approach and cohesive zone model. (15th December 2017) - Carollo, V.; Reinoso, J.; Paggi, M.
Abstract: In this study, a new 3D finite element formulation which enables simulating the interaction between brittle crack propagation and interface delamination in heterogeneous materials is presented. The Phase Field (PF) model for brittle fracture has been coupled with the Cohesive Zone Model (CZM) within the framework of the large deformation analysis. These numerical techniques have been implemented within a 8-node locking-free solid shell element, relying on the enhanced assumed strain concept, and a 8-node interface finite element, respectively. The predictive capabilities of the proposed formulation have been assessed through the simulation of cracking in flat and curved geometries under in-plane and out-of-plane loading conditions. The results show the ability of the model to predict complex crack paths where intralayer crack propagation and delamination occur simultaneously and interact. The proposed formulation provides a powerful modeling tool for the simulation of fracture phenomena in heterogeneous materials and laminate structures, which are characterized by the existence of numerous interfaces, such as in photovoltaic laminates.